A Delphi study of business models for cycling urban mobility platforms. (December 2022) - Sá, Elisabete; Carvalho, Ana; Silva, Joaquim; Rezazadeh, Arash
Abstract: The movement towards sustainable and liveable cities is gaining momentum and is projected to continue to shape the future of cities. Bicycles are one of the fastest-growing transportation modes that can contribute to more sustainable and smart urban mobility. New digital service platforms will likely arise to support an enhanced cycling mobility experience while also offering value to other stakeholders of a connected urban mobility ecosystem. Exploring suitable business models is critical to sustaining digital urban mobility platforms, but approaches that consider multiple stakeholders are scarce in previous research. Aiming to reduce this gap, this Delphi research with experienced professionals and academics adopts an ecosystem approach and explores two important components of business models for future cycling urban mobility platform services and the data they would generate: value propositions and value capture models. Results show that experts participating in the study generally agree on the potential attractiveness of the services of such a platform and mobility data for the studied stakeholders. However, lower and diverging estimates regarding the expected willingness to pay suggest that a business model that combines revenues from platform services and data services may be needed and that cross-subsidisation of some stakeholders could be necessary.